The Origins of Concrete Construction in Roman Architecture : Technology and Society in Republican Italy - Mogetta, Marcello (Cambridge University Press, 2021)
Cover -- Half-title page -- Title page -- Copyright page -- Contents -- List of Plates -- List of Figures -- List of Tables -- Acknowledgments -- One Introduction -- Aims and Methods -- Ground Rules: The Building Industry of Republican Rome and Italy -- Basic Terms and Definitions: What Is Roman Concrete? -- The Structura Caementorum in Republican Architecture: Techniques and Processes -- Dating Concrete Construction: A New Typological Approach -- The Structure of the Book -- Two Deconstructing Roman Concrete -- Roman Concrete and Roman Culture: Words and Things -- Roman Concrete and Roman Imperialism: Modern Perceptions -- Roman Concrete and Identity Construction: Ancient Representations -- Conclusions -- Three A New Date for Concrete in Rome -- At the Roots of Roman Republican Architecture -- The Local Environment: Sources of Building Materials in the Region of Rome -- Dating Early Concrete Construction in Rome: The Problem of the Porticus Aemilia -- Redating the Early Development of Concrete Construction in Rome: The Public Monuments -- Archaeometric Evidence on the Early Development of Mortars in Public Building -- Redating the Early Development of Concrete Construction in Rome: The Houses -- The Social and Cultural Context of the Technological Innovation -- Conclusions -- Four A View from the Suburbium -- Roman Republican Villas and Technological Innovation: Previous Approaches -- Agricultural Intensification and the Supply of Lime -- Building Techniques in the Volcanic Region: Villa Architecture in the Environs of Rome -- Concrete Construction and Urban Development in the Limestone Region: Tibur -- Building Techniques and Republican Villas in the Ager Tiburtinus -- The Villa Architecture of the Ager Tiburtinus in its Regional Setting -- Conclusions -- Five Building Samnite Pompeii -- Pre-Roman Pompeii and Roman Republican Architecture.